Odpowiedź :
Odpowiedź:
No to tak
1)
[tex]2(3-x)+7 = 4x-5(2+x) \\6-2x+7 = 4x-10-5x\\-2x+13 = -x-10 \\-x = -23 \\x = 23[/tex]
2)
[tex]2(x+4) - 1 = 5x+2 \\2x+8 - 1 = 5x+2 \\2x+7 = 5x+2\\3x= 5 \\x = \frac{5}{3 }[/tex]
Jakbyś czegoś tutaj nie rozumiał to napisz spróbuję to bardziej rozpisać.
Szczegółowe wyjaśnienie:
Odpowiedź:
2( 3-x) +7 = 4x - 5( 2+x)
6 -2x +7= 4x -10 -5x
-2x -4x +5x = - 10-7 -6
-x= -23 /*(-1)
x= 23
spr... 6- 2*23 +7= 4*23 -10- 5*23
6- 46 +7= 92- 10 -115
-33 = -33
L=P
2( x+4) -1 = 5x +2
2x +8 -1= 5x+2
2x -5x= 2 -8 +1
-3x= -5 /*(-1)
3x= 5 /:3
x=5/3= 1 i 2/3
spr.. 2* 5/3 +8-1= 5*5/3 +2
10/3 + 7= 25/3+2
3 i 1/3 +7= 8 i 1/3+2
10 i 1/3= 10 i 1/3
L=P
Szczegółowe wyjaśnienie: